Katalocu'l-levehâti'l-fâize fi'l-müsâbakati'd-devliyyeti's-sâminiyye li fenni'l-hatti bi-ismi'l-Bedevî ed-Dîrenî, 1312-1387 H. / 1894-1967 M. = Catalogue of winners' plates in the Eighth International Calligraphy Competition in the name of Badawi al-Dirani = Bedevî el-Diranî Milletlerarası Sekizinci Hat Yarışması kazanan eserler kataloğu / i'dâd Muhammed et-Temîmî ; takdîm = preface = önsöz Halit Eren. (İstanbul)
[13], 80 s.